Role of the p38 MAPK/C/EBPβ Pathway in the Regulation of Phenotype and IL-10 and IL-12 Production by Tolerogenic Bone Marrow-Derived Dendritic Cells - Chantal Guindi; Alexandre Cloutier; Simon Gaudreau; Echarki Zerif; Patrick P. McDonald; Olga Tatsiy; Claude Asselin; Gilles Dupuis; Denis Gris; Abdelaziz Amrani (Cells, 2018)
Dendritic cells (DCs) play a major role in innate and adaptive immunity and self-immune tolerance. Immunogenic versus tolerogenic DC functions are dictated by their levels of costimulatory molecules and their cytokine expression profile. The transcription factor C/EBPβ regulates the expression of several inflammatory genes in many cell types including macrophages. However, little is known regarding the role of C/EBPβ in tolerogenic versus immunogenic DCs functions. We have previously reported that bone marrow-derived DCs generated with GM-CSF (GM/DCs) acquire the signature of semi-mature tolerogenic IL-10-producing DCs as opposed to immunogenic DCs generated with GM-CSF and IL-4 (IL-4/DCs). Here, we show that tolerogenic GM/DCs exhibit higher levels of phosphorylation and enhanced DNA binding activity of C/EBPβ and CREB than immunogenic IL-4/DCs. We also show that the p38 MAPK/CREB axis and GSK3 play an important role in regulating C/EBPβ phosphorylation and DNA binding activity. Inhibition of p38 MAPK in GM/DCs resulted in a drastic decrease of C/EBPβ and CREB DNA binding activities, a reduction of their IL-10 production and an increase of their IL-12p70 production, a characteristic of immunogenic IL-4/DCs. We also present evidence that GSK3 inhibition in GM/DCs reduced C/EBPβ DNA binding activity and increased expression of costimulatory molecules in GM/DCs and their production of IL-10. Analysis of GM/DCs of C/EBPβ−/− mice showed that C/EBPβ was essential to maintain the semimature phenotype and the production of IL-10 as well as low CD4+ T cell proliferation. Our results highlight the importance of the p38MAPK-C/EBPβ pathway in regulating phenotype and function of tolerogenic GM/DCs.